Cationic covalent organic framework nanofiber diaphragm as well as preparation method and application thereof
By using cationic covalent organic frame nanofibers in lithium battery separators, the problem of hindered lithium ion migration in traditional separators in quasi-solid electrolytes is solved, and efficient lithium ion transmission and battery performance improvement is achieved.
Patent Information
- Application Number
- CN202411766661.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Traditional polyolefin separators cannot effectively promote the migration of lithium ions in quasi-solid electrolytes, resulting in low capacity of lithium batteries and poor circulation temperature under high Curlunt.
The covalent organic frame was prepared by Schiff base reaction, and the azide cation was modified with click reaction to form a cationic covalent organic frame nanofiber separator, and prepared by electrospinning and hot pressing process.
The migration number and conductivity of lithium ions are improved, and the high specific capacity and cycling stability of lithium batteries are achieved under high current density.
Smart Images

Figure CN119601896A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery separators, and in particular to a cationic covalent organic framework nanofiber separator and a preparation method and application thereof. Background Art
[0002] The balance between high energy density and adequate safety is the focus of the current new generation of batteries. Lithium metal anode has the advantages of high theoretical specific capacity, low redox potential (-3.040V vs standard hydrogen electrode) and low density (0.59g cm-3), and has the potential to achieve high energy density. However, in terms of safety, due to the active characteristics of lithium metal, it is easy to produce byproducts during the charging and discharging process, and form lithium dendrites, which have the safety problem of penetrating the diaphragm and causing danger. In terms of improving the safety of lithium metal batteries, the development of high-performance solid electrolytes has become the most effective method. Among them, quasi-solid electrolytes are a type of solid electrolyte that can provide higher safety performance, but compared with liquid electrolytes, their lithium ion migration rate is significantly reduced, resulting in the battery being unable to achieve high-capacity fast charging. As the most important safety valve and ion transport layer in the battery, the diaphragm plays a key role in the ion mass transfer of the battery. The current commercial polyolefin diaphragms often have low ionic conductivity and lithium ion migration number due to their low porosity, making it difficult to achieve high lithium ion migration rate and uniform lithium deposition in the quasi-solid electrolyte system.
[0003] In recent years, covalent organic framework materials have attracted the attention of researchers in the functional modification of diaphragms due to their high temperature resistance, light weight, uniform pore size, and high porosity. The currently developed methods include coating method and phase separation method. Although the diaphragms prepared by these methods can have a high specific capacity at low current density, the capacity is severely attenuated at high current density, making it difficult to achieve safe and efficient operation of quasi-solid electrolyte lithium metal batteries at high current density. Therefore, how to design new covalent organic framework materials and diaphragm processing technology, while giving the diaphragm high lithium ion conductivity and high lithium ion migration number, and thus achieving safe, efficient and fast charging, is of great significance to the development of the field of quasi-solid-state lithium metal batteries.
[0004] Invention content: The technical problem to be solved by the present invention is that the traditional polyolefin separator cannot solve the problems of lithium ion migration obstruction and low lithium ion migration number in quasi-solid electrolytes, resulting in low capacity of lithium batteries at high coulomb and poor cycle temperature performance. The present invention prepares a cationic covalent organic framework as a functional particle, and prepares a cationic covalent organic framework nanofiber separator that can anchor anions and promote lithium ion migration through an electrospinning process.
[0005] The first aspect of the present invention provides a method for preparing a cationic covalent organic framework nanofiber membrane, characterized in that it comprises the following steps:
[0006] Step 1: Prepare a covalent organic framework (COFs-[C≡HC]) with a triple bond through a Schiff base reaction, and then modify the azide cation onto the covalent organic framework through a click reaction to prepare a new cationic covalent organic framework (ICOFs).
[0007] Step 2: Add a certain amount of ICOFs into a solution of polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF), mix and stir evenly to obtain a spinning solution.
[0008] Step 3: Prepare cationic covalent organic framework nanofiber membrane through electrospinning and hot pressing process.
[0009] Further: The specific step of the Schiff base reaction in step 1 is to disperse the monomer 1,3,5-tris(4-aminophenyl)benzene (112.4 mg, 0.32 mmol) and 2,5-bis(2-propynyl-1-yloxy)-1,4-benzenedicarboxylate (116.4 mg, 0.48 mmol) into o-dichlorobenzene / n-butanol (6 mL, volume ratio 1 / 1), ultrasonically treat for 10 minutes, and add acetic acid aqueous solution (0.8 mL, 12 M). The solution mixture was poured into a 20 mL stainless steel autoclave lined with Teflon and heated at 120 ° C for 72 hours. The solid was filtered out, washed with tetrahydrofuran and n-hexane, and then vacuum dried at 60 ° C for 12 hours to obtain COFs-[C≡HC].
[0010] Further: in the step 1, the azide cation is 2-azido-1,3-dimethylimidazolium hexafluorophosphate.
[0011] Further: The specific steps of the click reaction in step 1 are as follows: COFs-[C≡HC] (60 mg), cuprous iodide (6 mg), N,N-diisopropylethylamine (0.2 ml) and 2-azido-1,3-dimethylimidazolium hexafluorophosphate (308 mg) are added to tetrahydrofuran / acetonitrile (0.8 ml / 7.2 ml) under argon atmosphere, stirred at room temperature for 24 hours, filtered out the precipitate, washed with acetone, acetonitrile and tetrahydrofuran, and vacuum dried at 60°C for 12 hours to obtain ICOFs powder.
[0012] Furthermore: in the step 2, the mass of ICOFs accounts for 10% to 30% of the total mass of ICOFs and PAN, and the concentration of PAN in the DMF solution is 10% to 15%.
[0013] Further: the spinning parameters of the electrospinning method in step 3 are that the spinning rate is set to 0.8-2 mL h -1, the working voltage is 10-20 kV, the distance between the needle and the collector is 8-15 cm, the temperature is 20-30 ° C, and the humidity is 30-60 ° C.
[0014] Furthermore: the parameters of the hot pressing process in step three are pressure 1-5N and temperature 30-100°C.
[0015] The second aspect of the present invention provides an application of a cationic covalent organic framework nanofiber separator in a quasi-solid-state lithium battery.
[0016] Further: The electrolyte used to prepare the quasi-solid electrolyte is a 1M LiPF6 diethyl carbonate / ethylene carbonate (volume ratio = 1 / 1) solution, and the method is to add 5% N,N-dimethylacrylamide, 0.2% polyethylene glycol diacrylate and 0.2% azobisisobutyronitrile to the electrolyte to prepare a polymerization precursor solution.
[0017] Further: using the above-mentioned diaphragm, polymerization precursor liquid, positive electrode material, and negative electrode material, the specific steps are to drop the polymerization precursor liquid into the cationic covalent organic framework nanofiber diaphragm, assemble the button battery, and then carry out in-situ polymerization reaction at 60°C to obtain the quasi-solid-state lithium battery.
[0018] The present invention has the following advantages:
[0019] (1) The cationic covalent organic framework particles prepared by the present invention have good dispersibility and uniformity in the fiber membrane.
[0020] (2) The cationic covalent organic framework nanofiber membrane prepared by the present invention can effectively inhibit anion transmission, promote lithium salt dissociation, and increase the lithium ion migration number.
[0021] (3) The solid-state lithium battery provided by the present invention has high specific capacity and cycle stability at high current density.
[0022] (4) The preparation process of the present invention is simple, the equipment and machinery are mature, and the production can be expanded. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of Example 1 of the present invention.
[0024] Figure 2 Graphs of ionic conductivity and lithium ion transference number for Examples 1-3.
[0025] Figure 3 It is a rate diagram of the quasi-solid-state lithium battery prepared based on the diaphragms of Example 1, Comparative Example 1 and Comparative Example 2 in the application examples.
[0026] Figure 4It is a long cycle diagram of the quasi-solid-state lithium battery prepared based on the diaphragms of Example 1, Comparative Example 1 and Comparative Example 2 in the application example. DETAILED DESCRIPTION
[0027] In order to make the results of the present invention more convincing, the technical solution provided by the present invention is described in detail in combination with the embodiments. The following preferred examples are only for illustrating the present invention, but do not limit the protection scope of the present invention.
[0028] All reagents and instruments used in this example are directly available on the market.
[0029] Example 1
[0030] This example provides a method for preparing a cationic covalent organic framework nanofiber membrane, comprising the following steps:
[0031] (1) The monomers 1,3,5-tris(4-aminophenyl)benzene (112.4 mg, 0.32 mmol) and 2,5-bis(2-propyn-1-yloxy)-1,4-benzenedicarbaldehyde (116.4 mg, 0.48 mmol) were dispersed in o-dichlorobenzene / n-butanol (6 mL, volume ratio 1 / 1), ultrasonically treated for 10 minutes, and then an acetic acid aqueous solution (0.8 mL, 12 M) was added. The solution mixture was poured into a 20 mL Teflon-lined stainless steel autoclave and heated at 120°C for 72 hours. The solid was filtered out, washed with tetrahydrofuran and n-hexane, and then vacuum dried at 60°C for 12 hours to obtain COFs-[C≡HC].
[0032] (2) Under argon atmosphere, COFs-[C≡HC] (60 mg), cuprous iodide (6 mg), N,N-diisopropylethylamine (0.2 ml) and 2-azido-1,3-dimethylimidazolium hexafluorophosphate (308 mg) were added to tetrahydrofuran / acetonitrile (0.8 ml / 7.2 ml) and stirred at room temperature for 24 hours. The precipitate was filtered out and washed with acetone, acetonitrile and tetrahydrofuran. The precipitate was vacuum dried at 60°C for 12 hours to obtain ICOFs powder.
[0033] (3) Prepare a PAN solution with a mass fraction of 15%. Then add ICOFs with a mass fraction of 20% of the total mass of ICOFs and PAN into the PAN solution and stir evenly to form a spinning solution.
[0034] (4) 20% ICOFs / PAN nanofiber membrane was prepared by electrospinning. The spinning parameters of the electrospinning method were set at a spinning rate of 0.8 to 2 mL h -1 , the working voltage is 10-20 kV, the distance between the needle and the collector is 8-15 cm, the temperature is 20-30 ° C, and the humidity is 30-60 ° C.
[0035] (5) Finally, the cationic covalent organic framework nanofiber membrane was obtained by hot pressing at 70°C and 2N, and was recorded as 20% ICOFs / PAN.
[0036] Example 2
[0037] This example provides a method for preparing a cationic covalent organic framework nanofiber membrane, which specifically refers to Example 1, except that the mass fraction of ICOFs in step (3) is changed to 10%, recorded as 10% ICOFs / PAN.
[0038] Example 3
[0039] This example provides a method for preparing a cationic covalent organic framework nanofiber membrane, which is specifically referred to Example 1, except that the mass fraction of ICOFs in step (3) is changed to 30%, recorded as 30% ICOFs / PAN.
[0040] Comparative Example 1
[0041] The commercially available model is Celgard 2400 PP separator.
[0042] Comparative Example 2
[0043] The PAN nanofiber membrane provided in this example is specifically referred to Example 1, except that ICOFs are not added in step (3).
[0044] from Figure 1 It can be seen from the scanning electron microscope image that the ICOFs particles in Example 1 (20% ICOFs / PAN) are uniformly dispersed in the nanofiber membrane, proving that ICOFs have good dispersibility and processability. Figure 3 The ionic conductivity and lithium ion migration number of Examples 1-3 and Comparative Example 2 were tested. When the content of ICOFs was 20%, the maximum ionic conductivity was 1.95 mS / cm, and the maximum lithium ion migration number was 0.74, which were significantly higher than 1.24 mS / cm and 0.55 of Comparative Example 2, indicating that the imidazolium cationic groups in ICOFs can effectively fix anions to promote the rapid transmission of lithium ions.
[0045] Application Examples
[0046] The present invention provides a method for preparing a quasi-solid-state lithium battery of a cationic covalent organic framework nanofiber separator, comprising the following steps:
[0047] (1) Prepare a polymerization precursor solution by adding 5% N,N-dimethylacrylamide, 0.2% polyethylene glycol diacrylate and 0.2% azobisisobutyronitrile into 1M LiPF6 diethyl carbonate / ethylene carbonate (volume ratio = 1 / 1) electrolyte and stirring for 20 minutes.
[0048] (2) The polymerization precursor solution is added dropwise to the separators prepared in Examples 1-3 and Comparative Examples 1-2, and button cells are assembled, followed by in-situ polymerization at 60° C. for 2 hours to obtain a quasi-solid-state lithium battery, wherein the positive electrode is NCM811 and the negative electrode is lithium metal.
[0049] The quasi-solid-state lithium battery based on the separators of Example 1 (20% ICOFs / PAN), Comparative Example 1 (PP), and Comparative Example 2 (PAN) was subjected to rate and cycle tests. Figure 3 The specific capacities of Example 1 at 0.5C, 1C, 2C, 3C, and 5C are 175.2 mAh g -1 、161.3mAh g -1 , 149.1mAh g -1 , 143.0mAh g -1 and 131.8mAh g -1 , which is significantly higher than the 160.6 mAh g in Comparative Example 1. -1 , 148.5mAh g -1 、136.3mAh g -1 , 127.6mAh g -1 and 113.5mAh g -1 and 170.2 mAh g in Comparative Example 2 -1 , 160.4mAh g -1 , 148.4mAh g -1 , 138.5mAh g -1 , 121.7mAh g -1 .like Figure 4 At a high current density of 5C, after 300 cycles, the capacity retention rates of Example 1, Comparative Example 1, and Comparative Example 2 were 83.2%, 18.8%, and 34.3%, respectively. This proves that the cationic covalent organic framework nanofiber separator prepared by the present invention has excellent performance and great prospects in the application of quasi-solid-state lithium batteries.
[0050] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a cationic covalent organic framework nanofiber membrane, characterized in that: The steps include: Step 1: Prepare a covalent organic framework (COFs-[C≡HC]) with a triple bond through a Schiff base reaction, and then modify the azide cation onto the covalent organic framework through a click reaction to prepare a new cationic covalent organic framework (ICOFs). Step 2: Add a certain amount of ICOFs into a solution of polyacrylonitrile (PAN) in N,N-dimethylformamide (DMF), mix and stir evenly to obtain a spinning solution. Step 3: Prepare cationic covalent organic framework nanofiber membrane through electrospinning and hot pressing process.
2. The method for preparing a cationic covalent organic framework nanofiber membrane according to claim 1, characterized in that: The specific steps of the Schiff base reaction in step 1 are to disperse the monomers 1,3,5-tris(4-aminophenyl)benzene and 2,5-bis(2-propyn-1-yloxy)-1,4-benzenedicaldehyde into o-dichlorobenzene / n-butanol, use acetic acid aqueous solution as a catalyst, and react at 120°C for 48 to 72 hours. Then wash with tetrahydrofuran and n-hexane, filter, and vacuum dry to obtain COFs-[C≡HC].
3. The method for preparing a cationic covalent organic framework nanofiber membrane according to claim 1, characterized in that: In the step 1, the azide cation is 2-azido-1,3-dimethylimidazolium hexafluorophosphate.
4. The method for preparing a cationic covalent organic framework nanofiber membrane according to claim 1, characterized in that: The specific steps of the click reaction in step 1 are as follows: under an argon atmosphere, COFs-[C≡HC], cuprous iodide, N,N-diisopropylethylamine and 2-azido-1,3-dimethylimidazolium hexafluorophosphate are dispersed in tetrahydrofuran / acetonitrile, stirred at room temperature for 24 hours, washed with acetone, acetonitrile and tetrahydrofuran, filtered, and vacuum dried to obtain ICOFs.
5. The method for preparing a cationic covalent organic framework nanofiber membrane according to claim 1, characterized in that: In the step 2, the mass of ICOFs accounts for 10% to 30% of the total mass of ICOFs and PAN, and the concentration of the DMF solution of PAN is 10% to 15%.
6. The method for preparing a cationic covalent organic framework nanofiber membrane according to claim 1, characterized in that: The spinning parameters of the electrospinning method in step 3 are a spinning rate of 0.8 to 2 mL h -1 , the operating voltage is 10-20 kV, the distance between the needle and the collector is 8-15 cm, the temperature is 20-30 °C, and the humidity is 30-60 °C.
7. The method for preparing a cationic covalent organic framework nanofiber membrane according to claim 1, characterized in that: The parameters of the hot pressing process in step three are a pressure of 1 to 5N and a temperature of 30 to 100°C.
8. Use of a cationic covalent organic framework nanofiber separator according to any one of claims 1 to 7 in a quasi-solid-state lithium battery.
9. A quasi-solid-state lithium battery according to claim 8, characterized in that: The preparation method of the quasi-solid electrolyte is to add N,N-dimethylacrylamide, polyethylene glycol diacrylate, and azobisisobutyronitrile into an electrolyte and polymerize at 60°C for 2 to 4 hours. The electrolyte used to prepare the quasi-solid electrolyte is a 1M LiPF6 diethyl carbonate / ethylene carbonate (volume ratio = 1 / 1) solution.
10. The quasi-solid-state lithium battery according to claim 8, characterized in that: The positive electrode material used includes any one of lithium iron phosphate or nickel-cobalt-manganese ternary material electrodes, and the negative electrode material includes any one of metallic lithium, graphite, and silicon-carbon negative electrodes.
Citation Information
Patent Citations
Organic-inorganic hybrid diaphragm of lithium metal battery, preparation method of organic-inorganic hybrid diaphragm and lithium metal battery
CN114284638A
Quick-charging type full-covalent organic framework nanofiber organic battery and preparation method and application thereof
CN118919819A
Method for improving capacity retention of lithium secondary cell, separator for the same, manufacturing method for the separator, and secondary cell comprising the same
KR1020120121623A